Impact of iron fortification on anaemia and iron deficiency among pre-school children living in Rural Ghana - Tchum, S.T.; Arthur, F.K.; Adu, B.; Sakyi, S.A.; Abubakar, L.A.; Atibilla, D.; Amenga-Etego, S.; Oppong, F.B.; Dzabeng, F.; Amoani, B.; Gyan, T.; Arhin, E.; et al. (PLOS ONE, 2021)
Anaemia in young sub-Saharan African children may be due to the double burden of malaria and iron deficiency. Primary analysis of a double-blind, cluster randomized trial of iron con taining micronutrient powder supplementation in Ghanaian children aged 6 to 35 months found no difference in malaria risk between intervention and placebo groups. Here, we per formed a secondary analysis of the trial data to assess the impact of long-term prophylactic iron fortificant on the risk of iron deficiency and anaemia in trial subjects. This population based randomized-cluster trial involved 1958 children aged between 6 to 35 months, identi fied at home and able to eat semi-solid foods. The intervention group (n = 967) received a daily dose containing 12.5 mg elemental iron (as ferrous fumarate), vitamin A (400 μg), ascorbic acid (30 mg) and zinc (5 mg). The placebo group (n = 991) received a similar micro nutrient powder but without iron. Micronutrient powder was provided daily to both groups for 5 months. At baseline and endline, health assessment questionnaires were administered and blood samples collected for analysis. The two groups had similar baseline anthropome try, anaemia, iron status, demographic characteristics, and dietary intakes (p > 0.05). Of the 1904 (97.2%) children who remained at the end of the intervention, the intervention group had significantly higher haemoglobin (p = 0.0001) and serum ferritin (p = 0.0002) levels than the placebo group. Soluble transferrin receptor levels were more saturated among children from the iron group compared to non-iron group (p = 0.012). Anaemia status in the iron group improved compared to the placebo group (p = 0.03). Continued long-term routine use of micronutrient powder containing prophylactic iron reduced anaemia, iron deficiency and iron deficiency anaemia among pre-school children living in rural Ghana’s malaria endemic area.
Research Article